BRCA1/2 mutation analysis in 41 ovarian cell lines reveals only one functionally deleterious BRCA1 mutation. Issue 3 (31st January 2013) - Stordal, Britta; Timms, Kirsten; Farrelly, Angela; Gallagher, Danielle; Busschots, Steven; Renaud, Mickaël; Thery, Julien; Williams, Deborah; Potter, Jennifer; Tran, Thanh; Korpanty, Greg; Cremona, Mattia; et al.
Abstract : Mutations in BRCA1/2 increase the risk of developing breast and ovarian cancer. Germline BRCA1/2 mutations occur in 8.6–13.7% of unselected epithelial ovarian cancers, somatic mutations are also frequent. BRCA1/2 mutated or dysfunctional cells may be sensitive to PARP inhibition by synthetic lethality. The aim of this study is to comprehensively characterise the BRCA1/2 status of a large panel of ovarian cancer cell lines available to the research community to assist in biomarker studies of novel drugs and in particular of PARP inhibitors. The BRCA1/2 genes were sequenced in 41 ovarian cell lines, mRNA expression of BRCA1/2 and gene methylation status of BRCA1 was also examined. The cytotoxicity of PARP inhibitors olaparib and veliparib was examined in 20 cell lines. The cell line SNU‐251 has a deleterious BRCA1 mutation at 5564G > A, and is the only deleterious BRCA1/2 mutant in the panel. Two cell lines (UPN‐251 and PEO1) had deleterious mutations as well as additional reversion mutations that restored the protein functionality. Heterozygous mutations in BRCA1/2 were relatively common, found in 14.6% of cell lines. BRCA1 was methylated in two cell lines (OVCAR8, A1847) and there was a corresponding decrease in gene expression. The BRCA1 methylated cell lines were more sensitive to PARP inhibition than wild‐type cells. The SNU‐251 deleterious mutant was more sensitive to PARP inhibition, but only in a long‐term exposure to correct for its slow growth rate. Cell lines derived from metastatic disease are significantly more resistant to veliparib (2.0 fold p = 0.03) compared to those derived from primary tumours. Resistance to olaparib and veliparib was correlated Pearsons‐R 0.5393, p = 0.0311. The incidence of BRCA1/2 deleterious mutations 1/41 cell lines derived from 33 different patients (3.0%) is much lower than the population incidence. The reversion mutations and high frequency of heterozygous mutations suggest that there is a selective pressure against BRCA1/2 in cell culture similar to the selective pressure seen in the clinic after treatment with chemotherapy. PARP inhibitors may be useful in patients with BRCA1 deleterious mutations or gene methylation. Highlights: ► First study of BRCA1/2 mutation and methylation in ovarian cancer cell lines. ► BRCA1/2 mutations are much less common in cell lines than in the clinic. ► There is a selective pressure against BRCA1/2 mutations in cell culture. ► BRCA1/2 methylated and mutated cell lines are more sensitive to parp inhibitors.